2022
DOI: 10.1021/acssuschemeng.2c02785
|View full text |Cite
|
Sign up to set email alerts
|

High-Strength, Multifunctional, and Long Nanocellulose Hybrid Fibers Coated with Esterified Poly(vinyl alcohol)–Citric Acid–Lignin Resin

Abstract: In natural fiber-reinforced polymer composites, strong and tough nanocellulose long fibers (NCLFs) are in high demand. Despite the availability of diverse cellulose nanofiber (CNF) preparations, efficient production of continuous high-strength NCLFs remains a challenge. This study reports a synergistic approach that entails wet spinning and coating CNF with a bio-based and hydrogen-bonded polyvinyl alcohol–citric acid–lignin (H-PCL) resin followed by esterification at 180 °C to form esterified poly­(vinyl alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…When the films are partially dried and rolled on a Teflon rod, the straws can perfectly adhere at the edges through hydrogen bond reformation thus eliminating the need for adhesives and binders. Further, heat-treatment of the straws results to ester bond formation which boosts the bond strength 16 .…”
Section: Self-bonding Mechanism Of the Strawsmentioning
confidence: 99%
“…When the films are partially dried and rolled on a Teflon rod, the straws can perfectly adhere at the edges through hydrogen bond reformation thus eliminating the need for adhesives and binders. Further, heat-treatment of the straws results to ester bond formation which boosts the bond strength 16 .…”
Section: Self-bonding Mechanism Of the Strawsmentioning
confidence: 99%
“…17,18 Utilizing film-forming agents such as PVA and modifying lignin via esterification processes can enhance its film-forming ability and reactivity, thus favoring the fabrication of advanced composites. [19][20][21] With the advancements in technology, various highstrength CLFs have been fabricated. Though these filaments favor the fabrication of high-performance polymer composites for various applications, transferring the exceptional strength at the micro/nanoscale to the macroscale faces obstacles rooted in high fiber production costs, noneconomical pilot systems, variable fiber quality, and time-consuming modification approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Natural resources such as lignin have often been used to enhance the performance of green composites, although the rigid aromatic structure and heterogeneity of lignin limit its functionality. The modification of lignin via esterification [5,18,28,29] could help realize high-strength and green composites suitable for commercializing starch products and nanocellulose fiberreinforced polymer composites. So far, the conversion of starch into valuable green materials is not commercially profitable due to the low quality and strength of the final products.…”
Section: Introductionmentioning
confidence: 99%
“…[17] A little consideration has been shown that such high-strength filaments are suitable for fabricating advanced high-performance and all-green composites targeting a broad range of applications-structural engineering, aerospace, automobile, etc. When combined with the appropriate resins, nanocellulose-based filaments have the potential to produce high-strength and all-green composites [5,18] with a unique balance of durability and degradability.Recently, high-strength nanocellulose and green composite were fabricated using tough and strong biobased resin composed of polyvinyl alcohol, citric acid (CA), and lignin. [5] As proof of concept, the wet-spun nanocellulose filament was weaved into mats and used in composite fabrication with the resin via hand layup and hot press.…”
mentioning
confidence: 99%
See 1 more Smart Citation